2017
DOI: 10.3389/fneur.2017.00165
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Quantification of Eye-Movement Impairments after Pontine Hemorrhage

Abstract: IntroductionWe report a case of hypertrophic olivary degeneration due to pontine hemorrhage. A 59-year-old male with untreated hypertension suffered a primary pontine hemorrhage, which caused horizontal eye-movement limitation. Progressive neurological deterioration with involuntary eye and palatal movements began months after hemorrhage. This was accompanied by magnetic resonance imaging evidence of hypertrophic olivary degeneration at 4.5 months.BackgroundPrimary pontine hemorrhage often leads to impairment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…HT often materializes weeks to months after the GMT lesion [9,10] and has been documented as the sole HOD symptom following pontine hemorrhage [10][11][12] .Although PT and HT de ne HOD, their coexistence is not universal. Patients could present with a spectrum of other involuntary movements, but without PT and HT [13][14][15][16][17] . Ocular myoclonus often combined with palatal tremor, constitute oculopalatal myoclonus.…”
Section: Discussionmentioning
confidence: 99%
“…HT often materializes weeks to months after the GMT lesion [9,10] and has been documented as the sole HOD symptom following pontine hemorrhage [10][11][12] .Although PT and HT de ne HOD, their coexistence is not universal. Patients could present with a spectrum of other involuntary movements, but without PT and HT [13][14][15][16][17] . Ocular myoclonus often combined with palatal tremor, constitute oculopalatal myoclonus.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients’ tremors may only be observed in physical examinations, which makes it critical to monitor the occurrence of tremor phenomenology, even months after the initial insult[ 14 ]. An analysis by Suner et al [ 15 ] confirmed that brief weekly measurements with an eye-tracker may allow early detection of HOD. To sum up, when encountered with these abovementioned clinical manifestations, we need to consider HOD.…”
Section: Discussionmentioning
confidence: 99%